Compressor partition plate and preparation method and application thereof

By using the matrix structure of sheet pearlite and diffusely distributed spherical carbide particles in the compressor partition, combined with spherical annealing and stamping molding processes, the wear resistance of the partition plate during alternating load and friction wear is solved. , the high wear resistance and deformation resistance of the partition are achieved, and the manufacturing cost is reduced.

CN119308852APending Publication Date: 2025-01-14ANHUI MEIZHI PRECISION MFG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411435132.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When existing compressor partitions withstand alternating loads and friction wear, it is difficult to ensure that they have both high rigidity and good wear resistance. At the same time, the large thickness leads to high manufacturing costs.

Method used

The matrix structure of the flake pearlite and the diffusely distributed spherical carbide particles is controlled between 8-30%. The spherical annealing and stamping and normalizing treatment are combined to form a specific microstructure structure. To improve hardness and wear resistance.

Benefits of technology

The high wear resistance and deformation resistance of the compressor partition are achieved, which reduces the probability of wear between the piston and partition, reduces the thickness of the partition, reduces the manufacturing cost, and improves the reliability of the partition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119308852A_ABST
    Figure CN119308852A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of compressor partition plates, and particularly relates to a compressor partition plate and a preparation method and application thereof. A matrix structure of the compressor partition plate comprises flaky pearlite and dispersedly-distributed spherical carbide particles. In a matrix structure, the mass percent of the spherical carbide particles is 8-30%. Starting from material selection, a punch forming process and a heat treatment process are combined, particularly through a reasonable normalizing treatment process, matrix structure and hardness are adjusted, so that the mass ratio of spherical carbide particles in the compressor partition plate is 8-30%, the hardness is 210-300 HV1, and it is guaranteed that the compressor partition plate has good wear resistance; the abrasion probability between the piston and the partition plate is greatly reduced, and the reliability of the partition plate is improved. In addition, the Young modulus of the compressor partition plate ranges from 200 GPa to 215 GPa, the deformation resistance is good, the compressor partition plate can be further thinned on the basis of the thickness of a powder metallurgy partition plate, and the manufacturing cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of compressor partitions, and in particular relates to a compressor partition and a preparation method and application thereof. Background Art

[0002] Multi-cylinder rotary compressors have multiple compression chambers, and partitions are set between two adjacent cylinders to separate them. When a multi-cylinder rotary compressor is running, the compression chambers are in different states and the states are constantly changing. The working environment requires that the compressor partition must be able to withstand the friction and wear of the upper and lower pistons while bearing the alternating load. Therefore, rigidity and wear resistance are the key to ensuring the good reliability of the partition.

[0003] At present, in order to improve the rigidity and wear resistance of the partition, the reliability of the partition is usually improved by improving the structure of the partition. For example, some studies have used a method of splicing multiple sub-partitions to obtain compressor partitions. Although the splicing method of sub-partitions is convenient for assembly and disassembly and improves assembly efficiency, these partitions are usually prepared by powder metallurgy. In order to ensure the reliability of the partition, its thickness is generally thicker and the manufacturing cost is high.

[0004] Therefore, it is of great significance to provide a compressor partition plate with suitable hardness, good wear resistance and thin thickness. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art.

[0006] Accordingly, a first aspect of the present invention provides a compressor diaphragm.

[0007] Specifically, the matrix structure of the compressor partition includes lamellar pearlite and dispersed spherical carbide particles;

[0008] In the matrix structure, the mass percentage of the spheroidal carbide particles is 8-30%.

[0009] Specifically, the compressor partition of the present invention has a specific matrix structure, including lamellar pearlite and dispersed spherical carbide particles. The spherical carbide particles are the key factors affecting the friction and wear performance of the compressor partition. The dispersed spherical carbides with a specific proportion can be used as a hard particle reinforcement phase to improve the strength and hardness of the material, thereby enhancing the ability of the compressor partition to resist micro-deformation. Too many or too few spherical carbide particles will affect the hardness of the material, thereby affecting the wear resistance of the partition. For example, when there are too few spherical carbide particles, the matrix structure is mainly non-spheroidized carbides or all non-spheroidized carbides, which reduces the hardness and strength of the compressor partition, reduces the wear resistance, and thus reduces the reliability. The compressor partition of the present invention has a reasonable mass proportion of spherical carbide particles in the matrix structure, and the compressor partition has a suitable hardness, which can improve its wear resistance. At the same time, the Young's modulus of the compressor partition of the present invention is high and is not easy to deform. On the basis of ensuring reliability, the thickness can be further reduced, so that the compressor partition thickness is thinner, reducing manufacturing costs.

[0010] According to some embodiments of the present invention, the mass percentage of the spheroidal carbide particles is 12-30%.

[0011] According to some embodiments of the present invention, the mass percentage of the spheroidal carbide particles is 18-30%.

[0012] Specifically, the present invention has better microstructure characteristics by further limiting the mass percentage of spheroidal carbide particles, so that the compressor partition has a better hardness range, better improves wear resistance, and increases reliability in use.

[0013] According to some embodiments of the present invention, in the lamellar pearlite, strip-shaped cementite and strip-shaped ferrite are alternately distributed.

[0014] Specifically, the lamellar pearlite of the present invention is formed by alternating distribution of strip-shaped cementite and strip-shaped ferrite. In the process of friction and wear, the cementite strip-shaped structure of the lamellar pearlite of this morphology has better wear resistance than the ferrite strip-shaped structure. The ferrite strip-shaped structure is equivalent to a "soft phase" and is easy to wear during the process of friction and wear. More will be worn away to form pits. Correspondingly, the cementite strip-shaped structure appears as a protrusion at the microscopic level, so that the wear surface forms a microscopic morphology similar to a wave. The wavy microscopic morphology is beneficial in the friction pair with oil lubrication, because the pits have a certain oil storage function, which can accommodate lubricating oil, which is conducive to the establishment of a lubricating oil film on the friction surface, improves the lubrication conditions, and thus improves the wear resistance. At the same time, spherical carbide particles with a specific mass percentage are dispersed in the matrix structure, which can act as hard points in the structure to form hard "islands", further promoting the appearance of the above-mentioned wavy micromorphology. Moreover, they can also act as hard particle reinforcement phases to enhance the overall strength and hardness of the substrate, greatly improving the ability of the compressor partition to resist micro-deformation, thereby better improving the reliability of the partition.

[0015] According to some embodiments of the present invention, the raw material of the compressor diaphragm includes tool steel.

[0016] According to some embodiments of the present invention, the tool steel comprises carbon tool steel, and the mass percentage of carbon element in the carbon tool steel is greater than 0.77%.

[0017] Specifically, the mass percentage of carbon element in the carbon tool steel of the present invention is greater than 0.77%, and the high carbon content is beneficial to improving the hardness of the compressor partition, improving the wear resistance, and further improving the reliability during actual use.

[0018] According to some embodiments of the present invention, the mass percentage of carbon element in the carbon tool steel is greater than 0.8%.

[0019] According to some embodiments of the present invention, the mass percentage of carbon element in the carbon tool steel is greater than 0.8% and less than 1.35%.

[0020] According to some embodiments of the present invention, the Young's modulus of the compressor diaphragm is 200-215 GPa.

[0021] According to some embodiments of the present invention, the Young's modulus of the compressor diaphragm is 200-210 GPa.

[0022] According to some embodiments of the present invention, the hardness of the compressor partition is 210-300 HV1.

[0023] According to some embodiments of the present invention, the compressor partition has a hardness of 240-300 HV1.

[0024] According to some embodiments of the present invention, the compressor partition has a thickness of 5-7 mm.

[0025] According to some embodiments of the present invention, the compressor partition has a thickness of 5.5-6.5 mm.

[0026] Specifically, compared with the compressor partitions prepared by the powder metallurgy method in the prior art, the Young's modulus of the compressor partition of the present invention can reach more than 200 GPa, which is higher than the powder metallurgy parts (less than 160 GPa), and its deformation resistance is improved. The partition can be further thinned on the basis of the thickness of the powder metallurgy partition, and the thickness can be 5-7 mm, thereby reducing the manufacturing cost of the partition.

[0027] The second aspect of the present invention provides a method for preparing the compressor partition plate described in the first aspect of the present invention.

[0028] Specifically, the method for preparing the compressor partition comprises the following steps:

[0029] The raw materials are subjected to spheroidizing annealing, stamping forming and normalizing treatment to obtain the compressor partition plate.

[0030] Specifically, the present invention firstly adopts a spheroidizing annealing process to adjust the hardness of the material to make it more conducive to stamping, and transforms the structure into spheroidal pearlite, and then undergoes a stamping process to obtain a plate of the required size, and then performs normalizing treatment under specific process conditions to obtain lamellar pearlite and dispersed spheroidal carbide particles, and the mass content of the spheroidal carbide particles can be controlled between 8-30%, and a compressor partition with a hardness of 210-300HV1 is obtained. The partition within this hardness range has good wear resistance, can greatly reduce the probability of wear between the piston and the partition, and improve the reliability of the partition. That is, the present invention starts from the perspectives of material selection, molding process, heat treatment process, etc., while selecting a suitable molding process, focuses on improving the material structure performance through a heat treatment process, and improving the reliability of the partition, which provides another idea for the manufacture of the partition. In addition, on the basis of ensuring reliability, the thickness of the partition is relatively thin, which can reduce the manufacturing cost.

[0031] According to some embodiments of the present invention, the temperature of the normalizing treatment is 780-830° C., and the holding time of the normalizing treatment is 40-90 min.

[0032] According to some embodiments of the present invention, the temperature of the normalizing treatment is 790-820° C., and the holding time of the normalizing treatment is 45-85 min.

[0033] Specifically, the normalizing process directly affects the content of spherical carbide particles in the matrix structure after heat treatment, and the spherical carbide and its content are the key factors affecting the friction and wear performance of the partition. During the heat treatment process, the tool steel will undergo austenite transformation when heated in the high temperature section. The use of appropriate normalizing temperature and holding time can cause it to undergo incomplete austenite transformation, retaining the spherical carbides dispersed in the spherical pearlite matrix, and the structure that is normally transformed into austenite. During the air cooling process, according to the iron-carbon phase diagram and the hypereutectoid steel CCT curve (supercooled austenite continuous cooling transformation curve) phase transformation theory, it will eventually transform into lamellar pearlite with alternating distribution of strip-shaped cementite and strip-shaped ferrite. According to the above analysis, the lamellar pearlite with this structural feature has a wavy microscopic morphology. During the friction and wear process, a pit structure will form on the surface. The pit structure can accommodate lubricating oil, improve lubrication conditions, and improve wear resistance. At the same time, the spherical carbide particles dispersed in the matrix can act as hard points to form hard "islands", further promoting the appearance of the above-mentioned wavy micromorphology and enhancing the wear resistance of the partition. In addition, after normalizing treatment, a specific amount of dispersed spherical carbide particles can also act as a hard particle reinforcement phase to improve the overall strength and hardness of the substrate. In short, after reasonable normalizing treatment, the ability of the compressor partition to resist micro-deformation can be greatly improved, thereby better improving the reliability of the partition and meeting actual practical needs.

[0034] According to some embodiments of the invention, the raw material comprises tool steel.

[0035] According to some embodiments of the present invention, the tool steel comprises carbon tool steel, and the mass percentage of carbon element in the carbon tool steel is greater than 0.77%.

[0036] According to some embodiments of the present invention, the mass percentage of carbon element in the carbon tool steel is greater than 0.8%.

[0037] According to some embodiments of the present invention, the mass percentage of carbon element in the carbon tool steel is greater than 0.8% and less than 1.35%.

[0038] Specifically, from the perspective of material selection, the present invention selects a specific type of steel as the raw material, and combines the stamping process and the normalizing heat treatment process, especially the normalizing heat treatment process, to adjust the substrate structure characteristics and proportions, improve the material structure performance, and enhance the reliability of the partition.

[0039] According to some embodiments of the present invention, the spheroidizing annealing includes isothermal spheroidizing annealing.

[0040] According to some embodiments of the present invention, the isothermal spheroidizing annealing process is to first keep the temperature at 725-745° C. for 50-70 min, and then cool the temperature to 645-665° C. and keep the temperature for 25-35 min.

[0041] According to some embodiments of the present invention, the isothermal spheroidizing annealing process is to first keep the temperature at 730-740° C. for 55-65 min, then cool down to 650-660° C. and keep the temperature for 27-33 min.

[0042] According to some embodiments of the present invention, the hardness of the material after spheroidizing annealing is less than 80 HRB.

[0043] According to some embodiments of the present invention, the hardness of the material after spheroidizing annealing is greater than or equal to 60 HRB and less than 80 HRB.

[0044] According to some embodiments of the present invention, the hardness of the material after spheroidizing annealing is greater than or equal to 65 HRB and less than 80 HRB.

[0045] Specifically, spheroidizing annealing can spheroidize carbides in steel. Compared with ordinary spheroidizing annealing, the isothermal spheroidizing annealing under specific process conditions adopted in the present invention can not only shorten the cycle, but also make the spheroidized structure more uniform, and can strictly control the hardness after annealing, improve the plastic deformation ability, and facilitate the smooth progress of the subsequent stamping forming process.

[0046] According to some embodiments of the present invention, the stamping pressure is 50-60t.

[0047] According to some embodiments of the present invention, the stamping pressure is 55-60t.

[0048] According to some embodiments of the present invention, the stamping pressure is 60t.

[0049] According to some embodiments of the present invention, the cooling method of the spheroidizing annealing and the normalizing treatment is air cooling.

[0050] Specific and reasonable cooling methods can help obtain the desired microstructure and improve material properties.

[0051] A third aspect of the present invention provides a compressor.

[0052] Specifically, the compressor includes the compressor partition described in the first aspect of the present invention.

[0053] Specifically, the compressor partition provided by the present invention has good wear resistance and reliability in use, and after being applied to the compressor, it can meet the reliability requirements of the compressor.

[0054] A fourth aspect of the present invention provides a temperature adjustment device.

[0055] Specifically, the temperature regulating device includes the compressor described in the third aspect of the present invention.

[0056] According to some embodiments of the present invention, the temperature regulating device includes any one of an air-conditioning compressor and a refrigerator compressor.

[0057] Specifically, the mass proportion of spherical carbide particles in the compressor partition of the present invention is 8-30%, and the hardness is 210-300HV1, which ensures that the compressor partition has good wear resistance, greatly reduces the probability of wear between the piston and the partition, ensures the reliability of the compressor, and further ensures the reliability of temperature control equipment such as air conditioners and refrigerators during use, and achieves good temperature regulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a schematic diagram of the process flow of preparing a compressor partition plate according to Example 1 of the present invention;

[0059] Figure 2 This is a scanning electron microscope image of a compressor partition prepared in Example 2 of the present invention;

[0060] Figure 3 This is a surface laser confocal microscope test curve diagram of the compressor partition prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0061] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0062] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0063] A first aspect of an embodiment of the present invention provides a compressor partition plate, wherein the matrix structure of the compressor partition plate includes lamellar pearlite and dispersed spherical carbide particles; in the matrix structure, the mass percentage of the spherical carbide particles is 8-30%.

[0064] The compressor partition of the embodiment of the present invention has specific microstructure characteristics, including lamellar pearlite and dispersed spherical carbide particles, and the spherical carbide particles are the key factors affecting the friction and wear performance of the compressor partition. The dispersed spherical carbide can be used as a hard particle reinforcement phase to improve the strength and hardness of the material, thereby enhancing the ability of the compressor partition to resist micro-deformation. In addition, too many or too few spherical carbide particles will affect the hardness of the material, thereby affecting the wear resistance of the partition, and ultimately affecting the reliability of the compressor partition. For example, when there are too few spherical carbide particles, the matrix structure is mainly non-spheroidized carbide or all non-spheroidized carbide, which reduces the hardness and strength of the compressor partition, reduces the wear resistance, and thus reduces the reliability. The compressor partition matrix structure of the present invention has a reasonable mass ratio of spherical carbide particles, the compressor partition has a suitable hardness, can improve its wear resistance, and has a high Young's modulus and is not easy to deform. On the basis of ensuring reliability, the thickness can be further reduced, so that the compressor partition thickness is thinner, reducing manufacturing costs.

[0065] According to some embodiments of the present invention, the mass percentage of the spheroidal carbide particles is 12-30%.

[0066] According to some embodiments of the present invention, the mass percentage of the spheroidal carbide particles is 18-30%.

[0067] According to some embodiments of the present invention, the mass percentage of the spheroidal carbide particles may be selected from 8%, 10%, 12%, 15%, 18%, 20%, 25% or 30%.

[0068] The embodiment of the present invention further limits the mass percentage of the spheroidal carbide particles, which can maximize the strength and hardness of the compressor partition, thereby improving the wear resistance, and better meeting the reliability requirements of the compressor partition during actual use.

[0069] According to some embodiments of the present invention, in the lamellar pearlite, strip-shaped cementite and strip-shaped ferrite are distributed alternately.

[0070] The lamellar pearlite in the matrix structure of the embodiment of the present invention is formed by alternating distribution of strip-shaped cementite and strip-shaped ferrite. In the process of friction and wear, the lamellar pearlite with alternating distribution of strip-shaped cementite and strip-shaped ferrite has better wear resistance than the ferrite strip-shaped structure. The ferrite strip-shaped structure is equivalent to a "soft phase" and is easy to wear during the process of friction and wear. Relatively speaking, more will be worn away to form pits. Correspondingly, the cementite strip-shaped structure appears as protrusions at the microscopic level, so that the matrix wear surface forms a microscopic morphology similar to a wave. This wavy microscopic morphology is beneficial in oil-lubricated friction pairs, because the pits have a certain oil storage function and can accommodate lubricating oil, which is conducive to the establishment of a lubricating oil film on the friction surface, improves lubrication conditions, and thus improves wear resistance. At the same time, spherical carbide particles with a specific mass percentage are dispersed in the matrix structure, which can act as hard points in the structure to form hard "islands", further promoting the appearance of the above-mentioned wavy micromorphology. Moreover, they can also act as hard particle reinforcement phases to enhance the overall strength and hardness of the substrate, greatly improving the ability of the compressor partition to resist micro-deformation, thereby better improving the reliability of the partition and meeting actual practical needs.

[0071] According to some embodiments of the present invention, the raw material of the compressor diaphragm includes tool steel.

[0072] According to some embodiments of the present invention, the tool steel comprises carbon tool steel.

[0073] According to some embodiments of the present invention, the mass percentage of carbon element in the carbon tool steel is greater than 0.77%.

[0074] The mass percentage of carbon element in the carbon tool steel in the embodiment of the present invention is greater than 0.77%, and the high carbon content is conducive to improving the hardness and wear resistance of the compressor partition, thereby improving the reliability during actual use. The present invention ensures that the compressor partition has a reasonable hardness and wear resistance by selecting a specific type of tool steel and combining it with a subsequent heat treatment process, thereby having good reliability and meeting the use requirements.

[0075] According to some embodiments of the present invention, the mass percentage of carbon element in the carbon tool steel is greater than 0.8%.

[0076] According to some embodiments of the present invention, the mass percentage of carbon element in carbon tool steel is greater than 0.8% and less than 1.35%.

[0077] According to some embodiments of the present invention, the carbon tool steel is SK85 (T8) tool steel.

[0078] According to some embodiments of the present invention, the Young's modulus of the compressor diaphragm is 200-215 GPa.

[0079] According to some embodiments of the present invention, the Young's modulus of the compressor diaphragm is 200-210 GPa.

[0080] According to some embodiments of the present invention, the Young's modulus of the compressor diaphragm is 206 GPa.

[0081] According to some embodiments of the present invention, the hardness of the compressor diaphragm is 210-300 HV1.

[0082] According to some embodiments of the present invention, the hardness of the compressor diaphragm is 240-300 HV1.

[0083] According to some embodiments of the present invention, the hardness of the compressor diaphragm may be 210 HV1, 243 HV1, 275 HV1, or 300 HV1.

[0084] According to some embodiments of the present invention, the compressor partition has a thickness of 5-7 mm.

[0085] According to some embodiments of the present invention, the compressor partition has a thickness of 5.5-6.5 mm.

[0086] According to some embodiments of the present invention, the compressor partition has a thickness of 5.5 mm.

[0087] Compared with the compressor partition of the embodiment of the present invention prepared by the powder metallurgy method in the prior art, the Young's modulus of the compressor partition of the embodiment of the present invention can reach more than 200GPa, which is higher than the powder metallurgy parts (less than 160GPa), and the hardness is 210-300HV1. Its deformation resistance is improved, and the partition can be further thinned on the basis of the thickness of the powder metallurgy partition to a thickness of 5-7mm, thereby reducing the manufacturing cost of the partition.

[0088] The second aspect of the present invention provides a method for preparing the compressor partition plate of the first aspect of the present invention, comprising the following steps:

[0089] The raw materials are subjected to spheroidizing annealing, stamping forming and normalizing treatment to obtain the compressor partition.

[0090] In the embodiment of the present invention, the raw material steel is first subjected to spheroidizing annealing to obtain a uniform spheroidized structure, so that the structure is converted into spheroidized pearlite, and the hardness after annealing can be reasonably adjusted and controlled to improve the plastic deformation ability, which is conducive to the smooth progress of the subsequent stamping process. Then, after the stamping process, a plate of the required size is obtained, and then normalizing treatment is performed under specific process conditions to obtain lamellar pearlite and dispersed spheroidal carbide particles. In addition, the proportion of the matrix structure can be adjusted by normalizing treatment, and the mass content of the spheroidal carbide particles can be controlled between 8-30%, so as to obtain a compressor partition with a hardness of 210-300HV1. The partition within this hardness range has good wear resistance, can greatly reduce the probability of wear between the piston and the partition, and improve the reliability of the partition. That is, the present invention starts from the perspectives of material selection, forming process, heat treatment process, etc., while selecting a suitable forming process, focuses on improving the material structure performance through heat treatment process, and improving the reliability of the partition, which provides another idea for the manufacture of the partition.

[0091] According to some embodiments of the present invention, the temperature of the normalizing treatment is 780-830° C., and the holding time of the normalizing treatment is 40-90 min.

[0092] According to some embodiments of the present invention, the temperature of the normalizing treatment is 790-820° C., and the holding time of the normalizing treatment is 45-85 min.

[0093] According to some embodiments of the present invention, the temperature of the normalizing treatment is 780° C., and the holding time of the normalizing treatment is 40 min.

[0094] According to some embodiments of the present invention, the temperature of the normalizing treatment is 780° C., and the holding time of the normalizing treatment is 90 min.

[0095] According to some embodiments of the present invention, the temperature of the normalizing treatment is 830° C., and the holding time of the normalizing treatment is 40 min.

[0096] According to some embodiments of the present invention, the temperature of the normalizing treatment is 830° C., and the holding time of the normalizing treatment is 90 min.

[0097] The embodiment of the present invention strictly controls the process parameters of the normalizing heat treatment, because the normalizing process directly affects the content of spheroidal carbide particles in the matrix structure of the partition after heat treatment, and the spheroidized carbide and its content are key factors affecting the friction and wear performance of the partition. During the heat treatment process, the tool steel will undergo austenite transformation when heated in the high temperature section. By adopting a suitable normalizing temperature and holding time, it can undergo incomplete austenite transformation, retain the spheroidal carbides dispersed in the spheroidal pearlite matrix, and normally transform into an austenite structure. During the air cooling and continuous cooling process, according to the iron-carbon phase diagram and the hypereutectoid steel CCT curve (supercooled austenite continuous cooling transformation curve) phase transformation theory, it is finally transformed into a lamellar pearlite with alternating distribution of strip-shaped cementite and strip-shaped ferrite. According to the above analysis, the lamellar pearlite with this structural feature has a wavy microscopic morphology, can accommodate lubricating oil, improve lubrication conditions, and improve wear resistance. At the same time, the spherical carbide particles dispersed in the matrix structure can serve as hard points in the structure to form hard "islands", further promoting the appearance of the above-mentioned wavy micromorphology, thereby further enhancing the wear resistance of the partition. In addition, after normalizing treatment, a specific content of dispersed spherical carbide particles can serve as a hard particle reinforcement phase in the matrix structure to improve the overall strength and hardness of the substrate. In short, after reasonable normalizing treatment, the ability of the compressor partition to resist micro-deformation can be greatly improved, thereby better improving the reliability of the partition and meeting actual practical needs.

[0098] According to some embodiments of the invention, the raw material includes tool steel.

[0099] According to some embodiments of the present invention, the tool steel comprises carbon tool steel, and the mass percentage of carbon in the carbon tool steel is greater than 0.77%.

[0100] From the perspective of material selection, the embodiment of the present invention selects a specific type of steel as the raw material. The mass percentage of carbon element in the raw material is greater than 0.77%, and the carbon content is relatively high, which is beneficial to improving the hardness and wear resistance of the compressor partition, thereby improving the reliability during actual use. At the same time, combined with the stamping forming process and the normalizing heat treatment process, especially the normalizing heat treatment process, the substrate tissue characteristics and ratio are adjusted, the material tissue performance is improved, and the reliability of the partition is enhanced.

[0101] According to some embodiments of the present invention, the mass percentage of carbon element in the carbon tool steel is greater than 0.8%.

[0102] According to some embodiments of the present invention, the mass percentage of carbon element in carbon tool steel is greater than 0.8% and less than 1.35%.

[0103] According to some embodiments of the present invention, the carbon tool steel is SK85 (T8) tool steel.

[0104] According to some embodiments of the present invention, the spheroidizing annealing includes isothermal spheroidizing annealing.

[0105] According to some embodiments of the present invention, the isothermal spheroidizing annealing process is to first keep the temperature at 725-745° C. for 50-70 minutes, and then cool the temperature to 645-665° C. and keep the temperature for 25-35 minutes.

[0106] According to some embodiments of the present invention, the isothermal spheroidizing annealing process is to first keep the temperature at 730-740° C. for 55-65 min, and then cool the temperature to 650-660° C. and keep the temperature for 27-33 min.

[0107] According to some embodiments of the present invention, the isothermal spheroidizing annealing process is to first keep the temperature at 735° C. for 60 minutes, and then cool the temperature to 655° C. and keep the temperature for 30 minutes.

[0108] According to some embodiments of the present invention, the hardness of the material after spheroidizing annealing is less than 80 HRB.

[0109] According to some embodiments of the present invention, the hardness of the material after spheroidizing annealing is greater than or equal to 60 HRB and less than 80 HRB.

[0110] According to some embodiments of the present invention, the hardness of the material after spheroidizing annealing is greater than or equal to 65 HRB and less than 80 HRB.

[0111] The spheroidizing annealing in the embodiment of the present invention can spheroidize the carbides in the steel. Compared with the ordinary spheroidizing annealing, the isothermal spheroidizing annealing under specific process conditions in the embodiment of the present invention can not only shorten the processing cycle, but also make the spheroidized structure more uniform, and can strictly control the hardness after annealing, improve the plastic deformation ability, and facilitate the smooth progress of the subsequent stamping process.

[0112] According to some embodiments of the present invention, the pressure of stamping is 50-60t.

[0113] According to some embodiments of the present invention, the pressure of stamping is 55-60t.

[0114] According to some embodiments of the present invention, the stamping pressure is 60t.

[0115] According to some embodiments of the present invention, a grinding process is further included after the normalizing treatment.

[0116] According to some embodiments of the present invention, the cooling method for spheroidizing annealing and normalizing treatment is air cooling.

[0117] The embodiment of the present invention adopts a reasonable cooling method after heat treatment to help obtain the desired microstructure and improve material properties.

[0118] Compared with the existing powder metallurgy process, the preparation process of the compressor partition of the embodiment of the present invention is simplified in the molding method. Secondly, the embodiment of the present invention uses SK85 (T8) tool steel as raw material, and its finished product Young's modulus (above 200GPa) is higher than that of powder metallurgy parts (less than 160GPa), and its anti-deformation ability is improved. Compared with the partition prepared by the powder metallurgy process, the present invention can reduce the thickness of the partition and reduce the production cost. Finally, through the appropriate heat treatment process, the morphology and proportion of carbides in the partition structure are adjusted to obtain a suitable overall hardness, which greatly reduces the probability of wear between the piston and the partition and improves the reliability of the partition.

[0119] A third aspect of the present invention provides a compressor.

[0120] A compressor according to an embodiment of the present invention includes the compressor diaphragm according to the first aspect of the present invention.

[0121] The compressor diaphragm of the embodiment of the present invention has good wear resistance and reliability in use. After being applied to the compressor, it can well meet the reliability of the compressor. After the compressor diaphragm of the embodiment of the present invention is applied to the compressor, it can run for 1000 hours at the maximum operating frequency and intermittent working conditions (i.e., running for 5 minutes and stopping for 5 minutes), and it passes smoothly without getting stuck. At the same time, in the high-frequency vacuum test (i.e., the compressor closes the suction valve and continues to run after the operation is stable), it operates normally within 300 seconds, without getting stuck, and the decomposed parts are not worn.

[0122] A fourth aspect of the present invention provides a temperature adjustment device.

[0123] A temperature adjustment device according to an embodiment of the present invention includes the compressor according to the third aspect of the present invention.

[0124] According to some embodiments of the present invention, the temperature regulating device includes any one of an air-conditioning compressor and a refrigerator compressor.

[0125] The mass proportion of spherical carbide particles in the compressor partition of the embodiment of the present invention is 8-30%, and the hardness is 210-300HV1, which ensures that the compressor partition has good wear resistance, greatly reduces the probability of wear between the piston and the partition, ensures the reliability of the compressor, and further ensures the reliability of temperature control equipment such as air conditioners and refrigerators during use, and achieves good temperature regulation.

[0126] The present invention is further described in detail below through specific examples and comparative examples.

[0127] Example 1

[0128] A method for preparing a compressor partition comprises the following steps:

[0129] The SK85 (T8) tool steel plate was subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process was to keep the plate at 735°C for 60 minutes, cool to 655°C for 30 minutes, take the plate out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate. The spheroidizing annealing plate was punched using a fine punching machine (the maximum punching pressure of the punch press was 60t) to obtain a formed partition. The formed partition was then normalized (the normalizing process was to keep the plate at 780°C for 40 minutes, and air-cool to room temperature) and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0130] Example 1 The schematic diagram of the preparation process of the compressor partition is as follows Figure 1 shown.

[0131] Example 2

[0132] A method for preparing a compressor partition comprises the following steps:

[0133] The SK85 (T8) tool steel plate was subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process was to keep the plate at 735°C for 60 minutes, cool to 655°C for 30 minutes, take the plate out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate. The spheroidizing annealing plate was punched using a fine punching machine (the maximum punching force of the punching machine is 60t) to obtain a formed partition. The formed partition was then normalized (the normalizing process was to keep the plate at 780°C for 90 minutes, and air-cool to room temperature) and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0134] Example 3

[0135] A method for preparing a compressor partition comprises the following steps:

[0136] The SK85 (T8) tool steel plate is subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process is to keep at 735°C for 60 minutes, cool to 655°C for 30 minutes, take out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate, and the spheroidizing annealing plate is punched by a fine punching machine (the maximum punching force of the punch is 60t) to obtain a formed partition, and then the formed partition is normalized (the normalizing process is to keep at 830°C for 40 minutes, and air-cool to room temperature), and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0137] Example 4

[0138] A method for preparing a compressor partition comprises the following steps:

[0139] The SK85 (T8) tool steel plate was subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process was to keep the plate at 735°C for 60 minutes, cool to 655°C for 30 minutes, take the plate out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate. The spheroidizing annealing plate was punched by a fine punching machine (the maximum punching force of the punching machine was 60t) to obtain a formed partition. The formed partition was then normalized (the normalizing process was to keep the plate at 830°C for 90 minutes, and air-cool to room temperature) and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0140] Comparative Example 1

[0141] The difference between Comparative Example 1 and Example 4 is that the insulation time during the normalizing treatment of the formed partition in Comparative Example 1 is 120 minutes.

[0142] Specifically, the preparation method of the compressor partition plate of Comparative Example 1 comprises the following steps:

[0143] The SK85 (T8) tool steel plate is subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process is to keep at 735°C for 60 minutes, cool to 655°C for 30 minutes, take out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate, and the spheroidizing annealing plate is punched by a fine punching machine (the maximum punching force of the punch is 60t) to obtain a formed partition, and then the formed partition is normalized (the normalizing process is to keep at 830°C for 120 minutes, and air-cool to room temperature), and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0144] Comparative Example 2

[0145] The difference between Comparative Example 2 and Example 1 is that the insulation time during the normalizing treatment of the formed partition in Comparative Example 2 is 30 minutes.

[0146] Specifically, the preparation method of the compressor partition plate of Comparative Example 2 comprises the following steps:

[0147] The SK85 (T8) tool steel plate is subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process is to keep at 735°C for 60 minutes, cool to 655°C for 30 minutes, take out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate, and the spheroidizing annealing plate is punched by a fine punching machine (the maximum punching force of the punch is 60t) to obtain a formed partition, and then the formed partition is normalized (the normalizing process is to keep at 780°C for 30 minutes, and air-cool to room temperature), and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0148] Comparative Example 3

[0149] The difference between Comparative Example 3 and Example 1 is that the temperature of normalizing the formed partition in Comparative Example 3 is 750°C.

[0150] Specifically, the preparation method of the compressor partition of comparative example 3 comprises the following steps:

[0151] The SK85 (T8) tool steel plate is subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process is to keep at 735°C for 60 minutes, cool to 655°C for 30 minutes, take out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate, and the spheroidizing annealing plate is punched by a fine punching machine (the maximum punching force of the punch is 60t) to obtain a formed partition, and then the formed partition is normalized (the normalizing process is to keep at 750°C for 40 minutes, and air-cool to room temperature), and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0152] Comparative Example 4

[0153] The difference between Comparative Example 4 and Example 3 is that the temperature of normalizing the formed partition in Comparative Example 4 is 860°C.

[0154] Specifically, the preparation method of the compressor partition of Comparative Example 4 comprises the following steps:

[0155] The SK85 (T8) tool steel plate is subjected to isothermal spheroidizing annealing (the isothermal spheroidizing annealing process is to keep at 735°C for 60 minutes, cool to 655°C for 30 minutes, take out of the furnace, and air-cool to room temperature) to obtain a spheroidizing annealing plate, and the spheroidizing annealing plate is punched by a fine punching machine (the maximum punching force of the punch is 60t) to obtain a formed partition, and then the formed partition is normalized (the normalizing process is to keep at 860°C for 40 minutes, and air-cool to room temperature), and ground to obtain a compressor partition with a thickness of 5.5 mm.

[0156] Performance Testing

[0157] 1. Scanning electron microscopy observation

[0158] The compressor partition obtained after normalizing treatment in Example 2 was observed and analyzed by scanning electron microscope. The scanning electron microscope image is as follows: Figure 2 As shown, Figure 2 Figure (a) is a scanning electron microscope image of the compressor partition plate of Example 2 after normalizing treatment. Figure 2 Figure (b) shows Figure 2 Enlarged view of the box in (a).

[0159] Depend on Figure 2It can be seen that there are lamellar pearlite and dispersed spherical carbide particles in the matrix structure of the compressor partition, and the lamellar pearlite is composed of alternating distribution of strip-shaped cementite and strip-shaped ferrite.

[0160] 2. Surface laser confocal microscopy test

[0161] The surface laser confocal microscopy test of the compressor partition prepared after normalizing treatment in Example 2 is performed. The curve of the surface laser confocal microscopy test of the compressor partition is as follows: Figure 3 shown.

[0162] Depend on Figure 3 It can be seen that the surface of the compressor partition prepared by the present invention has a low-lying morphology, which is because the lamellar pearlite in the matrix structure of the compressor partition is formed by alternating distribution of strip-shaped cementite and strip-shaped ferrite. During the friction and wear process, the lamellar pearlite with alternating distribution of strip-shaped cementite and strip-shaped ferrite has better wear resistance than the ferrite strip-shaped structure. The ferrite strip-shaped structure is equivalent to a "soft phase" and is easily worn during the friction and wear process, forming potholes. Correspondingly, the cementite strip-shaped structure appears as protrusions at the microscopic level, so that the matrix wear surface forms a microscopic morphology similar to a wave. This morphological feature can have a certain oil storage function, can accommodate lubricating oil, is conducive to the establishment of a lubricating oil film on the friction surface, improves lubrication conditions, and thus improves wear resistance.

[0163] 3. Test of hardness, Young's modulus and spheroidal carbide particle content of compressor diaphragm

[0164] The hardness, Young's modulus and spheroidal carbide particle content of the compressor partitions prepared in Examples 1-4 and Comparative Examples 1-4 were tested. The test methods of each test item are as follows:

[0165] Hardness: Tested using Vickers hardness measurement method;

[0166] Young's modulus: tested in accordance with GB / T 8653-2007;

[0167] Spheroidal carbide particle content: A 500x metallographic photograph was taken using a metallographic microscope, and the area occupied by different phases was determined by a binary method using the supporting software. The area ratio of the spheroidal carbide to the entire image was calculated as the content ratio of the spheroidal carbide.

[0168] The hardness, Young's modulus and the content of spherical carbide particles in the compressor partitions of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.

[0169] Table 1: Hardness, Young's modulus and content of spherical carbide particles in compressor diaphragms of Examples 1-4 and Comparative Examples 1-4

[0170]

[0171] It can be seen from Table 1 that in the compressor partitions of Examples 1-4 of the present invention, the mass proportion of spherical carbide particles is 8-30%, and the compressor partition has a hardness of 210-300 HV1 and a Young's modulus of 205-210 GPa, which has a relatively high Young's modulus.

[0172] The holding time of the normalizing treatment in Comparative Example 1 is 120 minutes, so that the mass proportion of spherical carbide particles in the compressor partition of Comparative Example 1 is 0%, that is, the carbides in the matrix structure are non-spheroidized and have a high hardness.

[0173] The holding time of the normalizing treatment in Comparative Example 2 is 30 minutes, so that the mass proportion of the spherical carbide particles in the compressor partition of Comparative Example 2 is 35%, that is, the mass proportion of the spherical carbide particles in the matrix structure is relatively large, and the hardness is relatively low.

[0174] The normalizing temperature of Comparative Example 3 is 750° C., so that the mass proportion of spherical carbide particles in the compressor partition of Comparative Example 3 is 38%, that is, the mass proportion of spherical carbide particles in the matrix structure is relatively large, and the hardness is relatively low.

[0175] The normalizing temperature of Comparative Example 4 is 750°C, so that the mass proportion of spheroidized carbide particles in the compressor partition of Comparative Example 4 is 3%, that is, the mass proportion of spheroidized carbide particles in the matrix structure is small, mainly non-spheroidized carbides, and the hardness is relatively high.

[0176] It can be seen from Table 1 that a reasonable normalizing treatment process can ensure that the mass proportion of spheroidal carbide particles in the compressor partition matrix structure is 8-30%. There is a close relationship between the organizational characteristics and performance of the material. By adjusting the mass proportion of spheroidal carbide particles, the hardness of the compressor partition is adjusted and the wear resistance is improved.

[0177] 4. Compressor reliability test

[0178] The compressor partitions prepared in Examples 1-4 and Comparative Examples 1-4 were assembled into a complete compressor in a conventional manner and then tested. The test items and methods are as follows:

[0179] Whole machine durability test: The compressors obtained by the compressor partitions of Examples 1-4 and Comparative Examples 1-4 are operated at the maximum operating frequency and intermittent operating conditions (run for 5 minutes, stop for 5 minutes), and the time when the compressor becomes stuck is recorded. If there is no sticking after 1000 hours of operation, the test is passed.

[0180] High-frequency vacuum test: The compressor obtained by the compressor partitions of Example 1-4 and Comparative Example 1-4 is subjected to high-frequency vacuum. After stable operation, the suction valve is closed and the operation is continued. If it operates normally within 300 seconds, there is no jamming, and the decomposed parts are not worn, the test is passed.

[0181] The reliability performance test results of the compressors obtained by the compressor partitions of Examples 1-4 and Comparative Examples 1-4 are shown in Table 2.

[0182] Table 2: Reliability performance test results of the compressors obtained by the compressor partitions of Examples 1-4 and Comparative Examples 1-4

[0183] Test items Whole machine durability test / h High frequency vacuum test / s Example 1 1000h passed 300s passed Example 2 1000h passed 300s passed Example 3 1000h passed 300s passed Example 4 1000h passed 300s passed Comparative Example 1 126h stuck Stuck Comparative Example 2 1000h passed Stuck Comparative Example 3 682 stuck Stuck Comparative Example 4 1000h passed Stuck

[0184] It can be seen from Table 2 that after the compressor partitions of Examples 1-4 of the present invention are applied to the compressor, they can successfully pass the whole machine endurance test and high-frequency vacuum test, indicating that Examples 1-4 can improve the wear resistance of the partitions and enhance the reliability of the compressor by adjusting the matrix structure and hardness. This is because the compressor partitions prepared by the present inventions 1-4 have reasonable hardness and correspondingly good wear resistance, which can ensure the reliability performance of the compressor.

[0185] The holding time of the normalizing treatment in Comparative Example 1 is 120 minutes, so that the compressor prepared by the compressor partition of Comparative Example 1 is stuck in both the whole machine endurance test and the high-frequency vacuum test.

[0186] The holding time of the normalizing treatment in Comparative Example 2 is 30 minutes, so the compressor prepared by the compressor partition of Comparative Example 2 is stuck in the high-frequency vacuum test.

[0187] The normalizing temperature of Comparative Example 3 is 750° C., so the compressor prepared by the compressor partition of Comparative Example 3 is stuck in both the whole machine endurance test and the high-frequency vacuum test.

[0188] The normalizing temperature of Comparative Example 4 is 750° C., so the compressor prepared by the compressor partition of Comparative Example 4 is stuck in the high-frequency vacuum test.

[0189] It can be seen from Table 2 that the present invention can improve the reliability performance of the compressor through a reasonable normalizing treatment process. This is because a reasonable normalizing treatment process can adjust the matrix structure and hardness. The mass proportion of spherical carbide particles in the matrix structure is 8-30%, the hardness is 210-300HV1, and the Young's modulus is 205-210GPa, which ensures that the compressor partition has good wear resistance and good deformation resistance. After applying it to the compressor, it can meet the reliability requirements of the compressor.

[0190] In summary, the embodiment of the present invention starts from material selection, and combines stamping forming process, heat treatment process, especially normalizing process, so that the mass proportion of spherical carbide particles in the compressor partition is 8-30%, and the hardness is 210-300HV1, which ensures that the compressor partition has good wear resistance, greatly reduces the probability of wear between the piston and the partition, and improves the reliability of the partition. In addition, because the Young's modulus of the compressor partition of the embodiment of the present invention is 200-215GPa, the deformation resistance is good, and the compressor partition can be further thinned on the basis of the thickness of the powder metallurgy partition, thereby reducing the manufacturing cost. Since the compressor partition has good wear resistance, the probability of wear between the piston and the partition is greatly reduced, the reliability of the compressor can be guaranteed, and then the reliability of temperature control equipment such as air conditioners and refrigerators can be guaranteed during use, and good temperature regulation can be achieved. In addition, since the thickness of the compressor partition of the embodiment of the present invention is thin, the manufacturing cost of the compressor can be reduced, thereby reducing the production cost of temperature control equipment such as air conditioners and refrigerators.

[0191] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A compressor partition, characterized in that: The matrix structure of the compressor partition plate includes lamellar pearlite and dispersed spherical carbide particles; In the matrix structure, the mass percentage of the spheroidal carbide particles is 8-30%.

2. The compressor diaphragm according to claim 1, characterized in that In the lamellar pearlite, strip-shaped cementite and strip-shaped ferrite are alternately distributed.

3. The compressor diaphragm according to claim 1, characterized in that The raw material of the compressor diaphragm includes tool steel.

4. The compressor diaphragm according to claim 3, characterized in that The tool steel comprises carbon tool steel, and the mass percentage of carbon element in the carbon tool steel is greater than 0.77%.

5. The compressor partition plate according to any one of claims 1 to 4, characterized in that: The Young's modulus of the compressor diaphragm is 200-215 GPa.

6. The compressor partition plate according to any one of claims 1 to 4, characterized in that: The hardness of the compressor partition is 210-300 HV1.

7. The compressor partition plate according to any one of claims 1 to 4, characterized in that: The compressor partition has a thickness of 5-7 mm.

8. The method for preparing a compressor partition according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials are subjected to spheroidizing annealing, stamping forming and normalizing treatment to obtain the compressor partition plate.

9. The preparation method according to claim 8, characterized in that: The temperature of the normalizing treatment is 780-830° C., and the holding time of the normalizing treatment is 40-90 min.

10. The preparation method according to claim 8, characterized in that: The spheroidizing annealing includes isothermal spheroidizing annealing.

11. The preparation method according to claim 10, characterized in that: The isothermal spheroidizing annealing process is to first keep the temperature at 725-745° C. for 50-70 minutes, and then cool the temperature to 645-665° C. and keep the temperature for 25-35 minutes.

12. The preparation method according to claim 8, characterized in that: The normalizing treatment also includes a grinding process.

13. A compressor, characterized in that: It comprises the compressor partition plate described in any one of claims 1 to 7, or the compressor partition plate prepared by the preparation method described in any one of claims 8 to 12.

14. A temperature regulating device, characterized in that: Comprising the compressor as claimed in claim 13.

15. The temperature regulating device according to claim 14, characterized in that Including any one of air-conditioning compressors and refrigerator compressors.